Ni-718 superalloy foam processed by powder space-holder technique: Microstructural and mechanical characterization - GÜLSOY, HAMİT ÖZKAN (REDAKCIA KOVOVE MATERIALY, 2021)
In this work, porous Ni-718 superalloys were produced by use of a water soluble pore forming agent before sintering. Carbamide particles were used as the space-holder material. After mixing and compaction, the space-holder particles were extracted using hot water leaching over a range of temperatures. The porous green parts were thermally debound to remove the paraffin wax under a pure argon atmosphere and then sintered at high vacuum. The effects of the volume fraction of space-holder particles on density and porosity were investigated. Microstructures were captured using optical and scanning electron microscopy. Also, compression tests were conducted on the sintered samples.
Keywords: superalloys; metal foam; sintering; STAINLESS-STEEL; SINTERING PROCESS; AL; PRECIPITATION; DISSOLUTION; STRENGTH; TITANIUM; SHAPE